Meningkatkan Aktivitas, Keterampilan Kerjasama dan Hasil Belajar Siswa Muatan PPKN Menggunakan Model BANUA - Umi Kaltsum; Aslamiah (CV. ITTC INDONESIA, 2023)
The research problem is the low student activity, cooperation skills and low student learning outcomes in PPKn content. This is because the learning process is less able to involve student activity, spurring students to study in groups and work together. One of the efforts made is through the use of the BANUA learning model. The purpose of this study was to describe teacher activities, increase student activity, student collaboration skills, and student learning outcomes. This study uses the type of Classroom Action Research by applying a qualitative research approach. The research subjects were fifth grade students at Sungai Miai 2 Elementary School, Banjarmasin. The results showed that the teacher's activities at meetings I to III obtained the criteria of